Facile and cost-effective manipulation of hierarchical carbon nanosheets for pseudocapacitive lithium/potassium storage. (15th September 2020) - Peng, Tingyue; Tan, Zhonghao; Zhang, Mengdi; Li, Linqing; Wang, Yixian; Guan, Lu; Tan, Xiaojie; Pan, Lei; Fang, Haiqiu; Wu, Mingbo
Abstract: The rising demand for high-performance energy storage devices calls for cost-effective electrode materials with large working potential windows, high specific capacities, and rapid rate capability. Herein, we propose a facile molten-salt-mediated production of ultrathin carbon nanosheets with tunable nitrogen doping using low-cost precursors including asphalt and melamine. The as-obtained nitrogen doped slim carbon nanosheets (NSCN) constructed through this easy and effective in-situ method offer both high specific capacity and excellent cycling stability. Specifically, a specific capacity of 848 mAh g −1 after 800 cycles at 1 A g −1 and 214 mAh g −1 after 1500 cycles at 1 A g −1 were achieved for lithium and potassium storage, respectively. The excellent electrochemical performances benefit from the synergistic effect of structural merits including ultra-thin nanosheet, nitrogen doping, high disorder degree and large specific surface area. Meanwhile, it also provides an avenue for realizing the value-added utilization of heavy oil in an alternative field. Graphical abstract: The synthetic process of the nitrogen-doped hierarchical carbon nanosheets is presented using a facile and cost-effective molten-salt approach. Image 1